A secure real-time internet of medical smart things (IOMST). (November 2018) - Farahat, I.S.; Tolba, A.S.; Elhoseny, Mohamed; Eladrosy, Waleed
Abstract: Cyber-attacks threat the IoMST since the day of its inception. Different threats and attacks may cause serious disasters to people and the network because of the lack of essential security protection. Thus, the security and the management of the IoMST become quite significant. This paper presents an approach to manage and secure the IOMST's data. A wireless system for medical data transfer must be secure through the authentication and data encryption processes. A new data encryption system is presented by first encoding data, then encrypting it with a rotated key before its transmission over the network. The physician restores the secure data by using his access credentials and digital signature. The proposed system is implemented using low-cost hardware and efficient software and proved to be secure in transmitting patient records.